2016
DOI: 10.1016/j.envres.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate pregnancy exposure and male offspring growth from the intra-uterine period to five years of age

Abstract: We highlighted associations between gestational exposure to some phthalates and growth in boys. The positive association between MEP and postnatal growth in boys was also reported in several previous human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 31 publications
2
51
2
2
Order By: Relevance
“…Our findings are consistent with those of Botton et al (17), who reported that prenatal urinary concentrations of MEP were associated with increased weight growth velocity at ages 2 and 4 years and increased BMI at 5 years in French boys ( N = 520). The study by Botton et al did not include girls and could not examine interaction by sex.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with those of Botton et al (17), who reported that prenatal urinary concentrations of MEP were associated with increased weight growth velocity at ages 2 and 4 years and increased BMI at 5 years in French boys ( N = 520). The study by Botton et al did not include girls and could not examine interaction by sex.…”
Section: Discussionsupporting
confidence: 93%
“…Five other investigations (1317) have used similar study designs as ours, measuring phthalate metabolites in prenatal urine and body weight in childhood, although no other study followed up children beyond 7 years of age. Our findings are consistent with those of Botton et al (17), who reported that prenatal urinary concentrations of MEP were associated with increased weight growth velocity at ages 2 and 4 years and increased BMI at 5 years in French boys ( N = 520).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Eden Mother-Child Cohort study, 520 mothers and children (of male sex only) were recruited and followed up for 5 years. Phthalate metabolites during pregnancy were positively linked to BMI at 5 years and to weight increase from 2 to 5 years of age in children [126].…”
Section: Impact On Offspring: Short-term and Long-term Outcomesmentioning
confidence: 95%